Psychological interventions for post-traumatic stress disorder in refugees and asylum seekers: A systematic review and meta-analysis. (July 2018) - Thompson, Christopher T.; Vidgen, Andrew; Roberts, Neil P.
Abstract: There is a high prevalence of post-traumatic stress disorder (PTSD) in refugee and asylum seeker populations which can pose distinct challenges for mental health professionals. This review included 16 randomised controlled trials (RCTs) with 1111 participants investigating the effect of psychological interventions on PTSD in these populations. We searched PsychInfo, ProQuest (including selected databases ASSIA, IBSS, PILOTS), Web of Science, the Cochrane Central Database of Controlled Studies (CENTRAL) and Cochrane Database for Systematic Reviews (CDSR) to identify peer-reviewed, primary research articles up to May 2018. We used rigorous methods to assess the quality of included trials and evidence using Cochrane, SURE and GRADE systems. 525 trials were reviewed, 16 were included with 15 contributed to meta-analyses. Despite the challenges of conducting research in this field we found evidence for trauma-focused psychological interventions for PTSD in this population. Following sub-group analyses, we found evidence to support the use of EMDR and Narrative Exposure Therapy for PTSD symptoms. We considered these findings in relation to the broader PTSD treatment literature and related literature from survivors of large scale conflict. These findings suggest that trauma focused psychological therapies can be effective in improving symptoms for refugees and asylum seekers with PTSD. Highlights: Increasing numbers of refugees and asylum seekers with complex needs. PTSD most-researched mental health condition for refugees. Available evidence to support use of trauma-focused psychological interventions. Lack of evidence for group-based or non-trauma-focused approaches at present. Evidence fairly consistent with the broader PTSD psychological intervention literature.